Akibat Hukum Penetapan Hak Waris Dan Hak Asuh Anak Oleh Hakim Pengadilan Negeri: Studi Putusan Nomor 282/Pdt.G/2014/Pn.Tng - Heru Siswanto; Elfirda Ade Putri (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2021)
Divorce causes various problems, one of which is the issue of determining child custody. In terms of determining child custody there are no definite rules regarding where the child will be anchored after the divorce, because Law No. 1 of 1974 concerning Marriage and Law No. 35 of 2014 concerning Child Protection do not regulate to whom the child is. Later, they will be cared for by both the father and mother. In child custody cases, the panel of judges usually refers to Jurisprudence and the Compilation of Islamic Law, but in one case there is something unique in the judge's decision which is more directed towards customary law so that it overrides these two things which are usually a reference in determining child custody. . So this is very important considering that in a problem the determination of child custody does not end after a court decision but how the parents who get the determination of child custody can fulfill especially the problem of fulfilling the rights and obligations of the child itself. Because it can be seen that children are victims of a divorce.